2022
DOI: 10.1080/17474086.2022.2029699
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated with immune thrombocytopenia: a systematic review and meta-analysis

Abstract: Background Immune thrombocytopenia, also known as immune thrombocytopenic purpura (ITP), has emerged as a significant COVID-19-associated complication. This study analyzes the published literature of case reports and case series regarding COVID-19 infection associated with ITP. Methodology In this systematic review and meta-analysis, a systematic search was conducted through PubMed, Web of Science, and Medline through Clarivate and EBSCO to include the eligible studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
5
34
0
1
Order By: Relevance
“…While low platelet counts can occur any time during the acute phase of COVID-19, it has been frequently observed after clinical recovery 50 , e.g. after three 51,52 or five weeks 53 after onset of symptoms, consistent with our findings. Further, we found significantly reduced levels of proteins of the actin cytoskeleton network amongst recuperated COVID-19 cases, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…While low platelet counts can occur any time during the acute phase of COVID-19, it has been frequently observed after clinical recovery 50 , e.g. after three 51,52 or five weeks 53 after onset of symptoms, consistent with our findings. Further, we found significantly reduced levels of proteins of the actin cytoskeleton network amongst recuperated COVID-19 cases, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…They also reported that none of the deaths in patients with COVID-19-induced ITP were associated with bleeding or ITP [14]. In addition, a recent systematic review and meta-analysis reported that most of the patients that had developed COVID-19-associated ITP recovered in less than one week [4]. Alonso-Beato et al reported an overall mortality of 7% in patients with COVID-19-induced ITP.…”
Section: Prognosis and Clinical Outcomementioning
confidence: 99%
“…A recent systematic review and meta-analysis reported that most of the patients that had developed COVID-19-associated ITP were male (54.8%) and over 50 years of age (median age of 63 years). In addition, most of the patients had developed ITP within 2-3 weeks after SARS-CoV-2 infection and recovered within a week [4].…”
Section: Covid-19-induced Immune Thrombocytopenicmentioning
confidence: 99%
See 2 more Smart Citations